Data Storage: Developing Biotemplated Data Storage: Room Temperature Biomineralization of L10 CoPt Magnetic Nanoparticles (Adv. Funct. Mater. 29/2015). (3rd August 2015) - Galloway, Johanna M.; Talbot, Jennifer E.; Critchley, Kevin; Miles, Jim J.; Bramble, Jonathan P.
Abstract : L10 CoPt can be used in data storage, but high temperatures (500 °C) are usually needed to achieve this. On page 4590, J. Galloway and colleagues demonstrate a bioinspired and ecological synthesis that uses a biotemplating peptide to form L10 CoPt nanoparticles at room temperature. A surface covered with biotemplated magnetic nanoparticles is illustrated in the back cover by Dr. Marcin Górzny (marcingorzny.com).